JINAYAT DALAM KITAB QONUN MELAKA - Riyadhi, Baidhillah; Mujahidah, Nelly (LP2M IAIN Mataram, 2012)
The notion of a sentence requires criminal sanctions are expected to be more effective to prevent the perpetrators from recommitting their actions. Therefore, there is a need for expansion of textual interpretation of the Koran and al-Hadith when in contact with local values and culture containing the same spirit, including the Book of Qanun Melaka, to achieve a sense of security and welfare. This research was conducted to examine some of the provisions contained in the book of Qanun Melaka, especially with regard to criminal law (jina>ya>t). These articles are related to punishment for crimes such as burglary, robbery, violence, and adultery. This research is a library research by examining the Book of Qanun Melaka as the primary data source. The secondary data sources were taken from variety of literature that examines Islamic law from a variety of schools thoughts. The structure of the book of Qanun Melaka illustrates the acceptance of Islamic law and the development of the Malay Islamic legal thought. Adoptation and selection of substance of customary law and Islamic law is one style of Qanun Melaka in realizing Melaka royal authority and the welfare of the Melaka community.